Medie imprese in sviluppo: gli assetti relazionali nei processi di integrazione post-acquisitiva - Tunisini, Annalisa; Bocconcelli, Roberta (Piccola Impresa / Small Business, 2013)
The paper discusses main problems occurring in the post-acquisition integration phase involving Italian mid-sized manufacturing companies. The research refers to 8 cases of Italian mid-large-sized companies acquiring Italian small-mid-sized companies in order to implement strategies of horizontal integration. The analysis highlights the difficulties connected to the valuable integration of the downstream and upstream business relationships of the acquiring and the acquired companies. The paper identifies two main factors affecting the difficulties of the post-acquisition integration of inter-organization assets – the distance in the management style of business relationships and the distance in their strategic focus in the acquiring and in the acquired companies